Use of The Combo Sealer Method Without a Neddle as an Innovation in Modern Circumcision - Taqwa, Muhammad; Setiawan, Bagas; Sary, Elsa Volinda; Yusprisan, Ajeng Ananda; Meinarisa, Meinarisa; Permata Sari, Yulia Indah (Jurusan Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2025)
In In the modern era, circumcision methods have undergone many innovations. However, the conventional methods that are still widely used often cause fear in children and slow down the recovery process, thereby disrupting daily activities. One innovative solution is the needle-free combo sealer method, which is minimally painful and accelerates healing. Unfortunately, this method is not yet widely known by the public, particularly in the city of Jambi and the surrounding areas of the Jami'atul Berkah Foundation. On the other hand, economic constraints remain the primary barrier for orphans and the underprivileged in accessing modern circumcision services. This community service initiative aims to assist them through health education and the implementation of circumcision procedures using the combo sealer method. Activities include counseling, informed consent, medication administration, procedures performed by professional medical staff, and outcome evaluation. This method has been proven to produce neater results, minimal bleeding, no stitches or bandages, and allows children to resume activities sooner.